Perlindungan Hukum Terhadap Pemilik Tanah Pada Perjanjian Pagang Gadai Masyarakat Hukum Adat Minangkabau di Nagari Koto Laweh Kabupaten Tanah Datar - Lesta, Arelita cheisya; Kurniawarman, Kurniawarman; Yasniwati, Yasniwati; Daswirman (UNES Law Review, 2024)
The pagang gadai activity has become its own tradition in the customary law society in Minangkabau and is still developing and living in the community. In carrying out the pawn there is an agreement between the pawn giver and the pawn holder based on the agreement of the two parties with the provisions and conditions that must be fulfilled by the two parties. So that the pawn agreement can be made in verbally and in writing. In the pagang gadai agreement agricultural land, field and fish ponds are the objects that will be handed over later to the pawn holder. Various problems then arise when this pawn practice regarding the party who doesn’t want to return the pawn’s object when it is redeemed. So that the problem is formulated: 1) How is the practice of pagang gadai in the Minangkabau customary law community in Nagari Koto Laweh Tanah Datar District. 2) How is dispute resolution to pagang gadai in the Minangkabau customary law community in Nagari Koto Laweh. 3) How is the position of high heirloom property when the pagang gadai is not redeemed by the landowner. This research used an empirical legal approach, by collected data through interviews and literature studies, and used qualitative analysis. The conclusion of this research is: 1) The practice of pagang gadai especially in Nagari Koto Laweh has used a written agreement even though there are stiil those who use it in verbally, pagang gadai is measured in gold units, provided that if the agreement is more than three gold the the pawn agreement must be made in writing. 2) Settlement of pagang gadai dispute is carried out of consensus, starting at the level of the community, tribe and finally reaching the Nagari level at Kerapatan Adat Nagari (KAN). 3) The position of high heirloom property which is the object of pagang gadai it will not change even if it is not redeemed by the landowner, not that its position will change because in the practice of pagang gadai in Minangkabau there is no time period.